BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KETIDAKMAMPUAN KONSTRUKSIONAL PADA PENDERITA STROK AKUT Dl BEBERAPA RUMAH SAKIT PENDIDIKAN DI MAKASSAR - Rahayu . (Saintika Medika, 2009)
To detect the prevalence of constructional inability on acute stroke patients and several factors associated with this inability. There is still insufficient study of constructional inability on acute stroke patients using the instrument of Clock DrawingTask. This study is a descriptive analysis crossectional study that was done on 62 acute stroke patients in the period of July - October 2002. Assesment of constructional inability using Clock Drawing Task. Relationship among the variables were statistically analyzed using Fisher Exact Test. Hipotesis is accepted if p < 0,05. From the 62 acute stroke patients observed, prevalence of the contructional inability was 88,72 % (55 patients). Relationship between constructional inability with site of lesion revealed p < 0,05, with the size of lesion on haemorhagik stroke p > 0,05 and with the size of lesion non haemorhagik stroke p > 0,05. The prevalence of contructional inability on acute stroke in this study was 88,7 %. There were significant relation between constructional inability with site of lesion and site of hemisphere. There was no significant between constructional inability with the size of lesion on both haemorhagik stroke and non haemorhagik stroke. Keyword : Constructional inability, acutestroke, Clock Drawing Task